ANALISIS SIFAT KIMIA TANAH GAMBUT PADA TIGA TIPE PENGGUNAAN LAHAN DI DESA PANGKALAN PANDUK KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - SAFRIZAL SAFRIZAL; OKSANA OKSANA; ROBBANA SARAGIH (Jurnal Agroteknologi, 2016)
This research was conducted from January until May 2015 at Pangkalan Panduk Village Kerumutan Subdistrict of Pelalawan Regency of Riau Province. The research aimed to determine the differences value pH, C-organik, KTK, N-total, P-total, and K-total at 0-50 cm, samples from forest peatlands, oil palm plantations at the age of 7 years and industrial forest plantations Acacia crassicarpa at the age of 6 years. The results showed an increase in pH by 0.03 % from peat forests into oil palm plantations and increased pH also occurs in peat forests into industrial forest by 0.96 %; an increase KTK of peat forests into oil palm plantations amounted to 22.62 mg/100g and peat forests into plantations amounting to 113.87 mg/100g; P-total increased from peat forests into oil palm plantations amounted to 22.62 mg/100g and peat forests into plantations also increased by 12.74 mg/100g; K-total increased from peat forests into oil palm plantations of 2.73 mg/100g and peat forests into plantations by also increased by 12.31 mg/100g. For C-organic chemical character changes occur perbedan where a decline of peat forests into oil palm plantations amounted to 11.15 % and an increase of C- organic peat forests into plantations by 0.05 % . Neither the N - total increased from peat forests into oil palm plantations of 0.51 % and a decline of peat forests into plantations by 0.31 %. We conclude changes in the chemical character of peat for all parameters measure were influenced by the changes in secondary forest peatland into oil palm plantations age of 7 years and plantation forests Acacia crassicarpa age 6 years.